PENGGUNAAN MEDIA SEMI KONKRIT DAN ANALOGI SEBAGAI UPAYA UNTUK MENINGKATKAN PEMAHAMAN KONSEP OPERASI HITUNG BILANGAN PECAHAN PADA SISWA KELAS 7E SMP NEGERI 36 SURABAYA - Purnawan Basundoro (JURNAL EDUKASI: KAJIAN ILMU PENDIDIKAN, 2018)
The purpose of this class action research is to improve the understanding of the concept of operating the fraction number in class 7E students of SMP Negeri 36 Surabaya by using semi-concrete media and analogies. The subjects of this class action research were 7E grade students of SMP Negeri 36 Surabaya, amounting to 40 students. The subjects implementing the action were the researchers and the subjects who helped the implementers were mathematics teachers and principals. Data is collected through tests and documentation. Descriptive qualitative data analysis with percentage of student learning outcomes. The results of this class action research are (1) Planning, (2) Implementation (action), (3) Observation (observation) and (4) Reflection. From the results of the classroom action research conducted by the researcher, the results obtained by increasing the completeness of learning outcomes are from 40% to 77.5% after the classroom action research cycle